13.3 MICROGLIAL DEREGULATION HYPOTHESIS IN PSYCHOSIS: A POSITRON EMISSION TOMOGRAPHY STUDY IN FIRST-EPISODE PSYCHOSIS AND LINKS TO CYTOKINE NETWORKS. (9th April 2019) - Hietala, Jarmo; Laurikainen, Heikki; Suvisaari, Jaana; Honkanen, Jarno; Haaparanta-Solin, Merja; Solin, Olof
Abstract: Background: A link between psychosis and neuroinflammation has been suggested. The microglial activation hypothesis of schizophrenia assumes in its simplest form that there is excessive microglial activation in schizophrenia. A leading concept in the microglia hypothesis is that the deregulation of these brain-resident macrophages affects normal patterns of CNS developmental and maturation including excessive pruning of synapses and formation of dysfunctional brain networks in schizophrenia. Microglial activity may play a role in defining clinical phenotypes of psychosis but may also be differentially active in various phases of psychotic disorders. The hypothesis of overactive microglia in psychosis has been recently contradicted and there is a methodological dispute around measuring microglial activation with PET and translocation protein (TSPO) tracers (1). Further in vivo glial cell data on patients with early psychosis and more detailed understanding of the links between TSPO binding and peripheral as well as central immune responses are urgently needed. Methods: We used 3D-PET and the second-generation TSPO tracer [11C]PBR28 as a glial cell marker in a sample of 14 patients with first-episode non-affective and affective psychosis and 16 healthy controls. Group effects of regional [11C]PBR28 PET distribution volume (VT) were tested with repeated measures ANOVA with TSPO binding genotype as a covariate. We further explored for an association of glial cell TSPO binding and cytokine network in serum and cell samples taken at the same time of PET scanning. The chemokine CCL-22 was of particular interest as it seems to be robustly elevated in first-episode psychosis along with other proinflammatory cytokines (2). Results: The results suggest a widespread decrease in [11C]PBR28 VT in first-episode psychosis compared to the control group with e.g. 24 % decrease in frontal cortex. We also explored the relationship of macrophage derived chemokine CCL-22 and VT of [11C] PBR28 starting with a larger sample of healthy controls in an assumed resting or 'homeostatic state'. Unexpectedly, higher CCL-22 levels predicted lower TSPO binding. Studies in patient samples and several cytokine networks as well as LPS activation studies in regulatory T-cells in relation to TSPO binding are underway. Conclusions: In contrast to the original microglial overactivation hypothesis, we suggest a reduced brain glial marker binding in patients in an early phase of a psychotic disorder despite elevated peripheral inflammatory markers. Our results are in good agreement with a recent mega-analysis on in vivo TSPO binding studies in psychosis (1). Unexpectedly, the levels of a chemokine CCL22 correlated negatively with brain TSPO binding. This suggests a complex relationship between TSPO binding and peripheral cytokine levels and emphasizes the need for studies on central and peripheral immune system interactions and their relevance for the etiology and possible treatment of psychotic disorders.